Lithium Isotopic Compositions of Mesozoic and Cenozoic Basalts From South-Eastern China: Implications for Extremely Low δ7Li of Continental-Type Eclogites - Yu, Cheng-Long; Xiao, Yilin; Wang, Yang-Yang; Nadeau, Olivier; Sun, He; Wan, Hong-Qiong; Li, Dong-Yong; Wang, Xiao-Xia; Tan, Dong-Bo (Frontiers in Earth Science, 2022)
Lithium isotope geochemical studies of oceanic-type eclogites benefited from previous investigation of altered oceanic crust; however, processes of lithium isotope exchange operating on altered protoliths of continental-type eclogites have remained unclear. Here, the Li concentration and isotopic composition of fresh and altered continental basalts from the South China Block were measured to decipher Li and its isotopic fractionation during subaerial alteration processes. The results show that altered South China basalts have higher Li concentration (11.4–117.7 ppm) and lower δ7Li values (−4.3–+0.5‰) than fresh basalts (Li: 5.0 ppm and δ7Li: ∼3‰). It is found that hydrothermal alteration played an important role in increasing the Li concentration of altered basalts, which is supported by the relation of loss on ignition and Li concentration. Subsequently, continental weathering acted on chlorite-bearing basalts, as evidenced by the occurrence of minor kaolinite and illite and weathering trend of δ7Li values in these basalts. Detailed petrography and in situ geochemical analyses are used to show that chlorite is the chief repository for Li in weathered basalts, supporting that it was responsible for decreasing δ7Li value by Rayleigh distillation during weathering. Because of the lower δ7Li values of continental altered basalts than oceanic altered crust, it is concluded that, in addition to the dehydration of subducted slabs and possible Li diffusion, the extremely light Li isotopic values of continental-type eclogites worldwide partly result from isotope fractionation caused by the continental weathering of their protoliths.